Analisis Kinerja Keuangan Dengan Metode Du Pont System (Studi Kasus Pada Perusahaan Pertambangan Sub Sektor Logam Dan Mineral Yang Terdaftar Di Bursa Efek Indonesia Periode 2019 2023 - Sulthon Fauzi, Armi; Made Dwi Sandi Saraswati (Al-Qardhu, 2025)
The purpose of this research is to analyzefinancial performance using the Du Pont System method. The Du Pont System method is a financial statement analysis technique that provides insights into a company's ability to enhance its return on equity. This research employs a quantitative descriptive method using secondary data in the form of financial statements of companies over the period from 2019 to 2023. Data collection techniques are conducted through literature studies and documentation. The population of this research consists of 35 companies in the metal and mineral sub-sector listed on the Indonesia Stock Exchange (/DX), while sample selection is carried out using purposive sampling, with a total sample of 5 companies. The indicators used are Net Profit Margin, Total Assets Turnover, Return On Investment, Equity Multiplier, and Return On Equity. The results of the study show that the financial performance of the sub• sector over the past 5 years has not been optimal compared to industry standards. The majority of the average values of the Du Pont System indicators for each company are still below industry standards, especially in NPM, TATO, ROI, and ROE. Companies need to improve operational efficiency, asset management, and capital returns to make their financial performance more competitive.